ENGLISH STRUCTURED SHOP NAMES IN THE USE OF INDONESIAN - Wijana, I Dewa Putu (Interling : International Journal of English Language Teaching, Literature and Linguistics, 2023)
This brief paper intends to describe the English structured shop names which are more and more to find in the use of Indonesian in the global era where the use of English has deeply penetrated the structure of world languages. By using samples of shop names found in Kalasan District and its adjacent areas, it is found that a lot of service and products used as the head of structure of noun phrase which are formerly constructed in post modifying pattern now has turned into premodifier one. And even more surprisingly, many Indonesian words are used as the head of phrase to refer to services and products offered following their attributes which refer to the names of the enterprise